Effects of DISC1 Polymorphisms on Resting-State Spontaneous Neuronal Activity in the Early-Stage of Schizophrenia - Gou, Ningzhi; Liu, Zhening; Palaniyappan, Lena; Li, Mingding; Pan, Yunzhi; Chen, Xudong; Tao, Haojuan; Wu, Guowei; Ouyang, Xuan; Wang, Zheng; Dou, Taotao; Xue, Zhimin; et al. (Frontiers in Psychiatry, 2018)
Background: Localized abnormalities in the synchrony of spontaneous neuronal activity, measured with regional homogeneity (ReHo), has been consistently reported in patients with schizophrenia (SCZ) and their unaffected siblings. To date, little is known about the genetic influences affecting the spontaneous neuronal activity in SCZ. DISC1, a strong susceptible gene for SCZ, has been implicated in neuronal excitability and synaptic function possibly associated with regional spontaneous neuronal activity. This study aimed to examine the effects of DISC1 variations on the regional spontaneous neuronal activity in SCZ. Methods: Resting-state fMRI data were obtained from twenty-eight SCZ patients and twenty-one healthy controls (HC) for ReHo analysis. Six single nucleotide polymorphisms (SNPs) of DISC1 gene were genotyped using the PCR and direct sequencing. Results: Significant diagnosis × genotype interactions were noted for three SNPs (rs821616, rs821617 and rs2738880). For rs821617, the interactions were localized to the precuneus, basal ganglia and pre/post-central regions. Significant interactive effects were identified at the temporal and postcentral gyri for rs821616 (Ser704Cys) and the inferior temporal gyrus for rs2738880. Furthermore, post-hoc analysis revealed that the DISC1 variations on these SNPs exerted different influences on ReHo between SCZ patients and HC. Conclusion: To our knowledge this is the first study to unpick the influence of DISC1 variations on spontaneous neuronal activity in SCZ; Given the emerging evidence that ReHo is a stable inheritable phenotype for schizophrenia, our findings suggest the DISC1 variations are possibly an inheritable source for the altered ReHo in this disorder.